STUDENTS' PERCEPTIONS OF DIY-SCIENCE EXPERIMENTS AS ASSIGNMENTS DURING COVID-19 PANDEMIC - Rani Oktavia; Rahmah Evita Putri; Arief Muttaqiin; Monica Prima Sari (SEMESTA: Journal of Science Education and Teaching, 2022)
Science learning cannot be separated from practical activities. Practical activities provide benefits for students as a vehicle to practice basic skills in conducting experiments which are very much needed as science student teacher. The Covid-19 pandemic has prevented lecture activities including practical work from being carried out in the laboratory as they should. As a solution, students continue to carry out practical work independently in their respective residences by using tools and materials that are easily found in the surrounding environment. This study aims to capture the perceptions of science education students who are enrolled in the school's science practicum lecture on the implementation of independent practical work based on materials, practical work guide, and the implementation. The research method used is descriptive research with a quantitative approach. The instrument used was an online questionnaire which was distributed to 95 respondents. The results showed that students' perceptions were quite diverse on materials, practicum guides, and the implementation.